2013
DOI: 10.1093/nar/gkt1152
|View full text |Cite
|
Sign up to set email alerts
|

Trans-splicing and RNA editing of LSU rRNA in Diplonema mitochondria

Abstract: Mitochondrial ribosomal RNAs (rRNAs) often display reduced size and deviant secondary structure, and sometimes are fragmented, as are their corresponding genes. Here we report a mitochondrial large subunit rRNA (mt-LSU rRNA) with unprecedented features. In the protist Diplonema, the rnl gene is split into two pieces (modules 1 and 2, 534- and 352-nt long) that are encoded by distinct mitochondrial chromosomes, yet the rRNA is continuous. To reconstruct the post-transcriptional maturation pathway of this rRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…Essentially all genes are broken up into up to 11 modules that are on average 170 bp long (43–534 bp; Table ) and whose breakpoints are apparently located at random positions. The only contiguous gene in D. papillatum mtDNA specifies the mitochondrial small subunit ribosomal RNA (mt‐SSU rRNA), which happens to be exceptionally short (366 bp)—to our knowledge, the smallest of its kind .…”
Section: Unusual Features Of the D Papillatum Mitochondrial Genomementioning
confidence: 99%
“…Essentially all genes are broken up into up to 11 modules that are on average 170 bp long (43–534 bp; Table ) and whose breakpoints are apparently located at random positions. The only contiguous gene in D. papillatum mtDNA specifies the mitochondrial small subunit ribosomal RNA (mt‐SSU rRNA), which happens to be exceptionally short (366 bp)—to our knowledge, the smallest of its kind .…”
Section: Unusual Features Of the D Papillatum Mitochondrial Genomementioning
confidence: 99%
“…2). 17 We demonstrated that Us are appended to the module upstream of the junction, before this terminus engages in trans-splicing. 14 Table 1.…”
Section: Trans-splicing Of Fragmented Genesmentioning
confidence: 86%
“…3 Therefore, we enriched mitochondrial transcripts by oligo(dT) purification, which facilitated their characterization via targeted RT-PCR 10,13,14 and transcriptomics. 11,17 In silico approaches A standard procedure in eukaryotic genomics is to generate reads by whole-genome/random-fragment approach and assemble these reads (ideally yielding chromosome-size contigs). Mapping of transcriptome (RNA-Seq) reads against the genome locates genes and introns and allows one to spot potential polymorphisms and RNA editing sites.…”
Section: Experimental/biochemistry Approachesmentioning
confidence: 99%
“…Like E. gracilis, two LSU fragments (534 and 352 nt) are present, encoded on two Class B chromosomes (Valach et al 2014). These RNAs are trans-spliced to produce a single LSU rRNA of approximately 900 nt and appear to go through other additional processing steps.…”
Section: Mitochondrial Ribosomal Rnamentioning
confidence: 99%